ANALISIS PENERAPAN REKAM MEDIS ELEKTRONIK (RME) TERHADAP KUALITAS PELAYANAN KESEHATAN MENGGUNAKAN METODE HUMAN ORGANISATION TECHNOLOGY-FIT (HOT-FIT) DI RSU MADANI MEDAN TAHUN 2025 - apriana, ana -; SEMBIRING, RIPANDO JHON SATRIA; Barus, Juni Kristin Br; Sinulingga, Emmenita Carian Br; Nazara, Helpi Lencani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
Digital transformation in the health sector requires health service facilities to adopt electronic medical records as an effort to increase efficiency, effectiveness and quality of service. This research aims to analyze the application of electronic medical records to the quality of health services using the human organization technology-fit method at RSU Madani Medan in 2025. This type of research is quantitative, cross sectional in nature. The population in this study was all 222 health workers who used electronic medical records. The sampling technique used was purposive sampling with a sample size of 69 employees. The measuring instrument used is a questionnaire sheet with a Guttman measurement scale. The results of data analysis were processed using SPSS with the Chi-Square test. Data obtained from the human aspect shows no influence of the implementation of RME on the quality of health services with a p-value of 0.760 > α 0.05. From the organizational aspect, there is no influence of the implementation of RME on the quality of health services with a p-value of 0.688 > α 0.05. From the technological aspect, there is an influence of the implementation of RME on the quality of health services with a p-value of 0.035 < α 0.05. From the net-benefit aspect, there is no effect of implementing RME on the quality of health services with a p-value of 0.804 > α 0.05. Suggestions for hospitals to pay more attention to the process of implementing electronic medical records so that electronic medical records can be fully optimized at RSU Madani Medan so as to increase patient satisfaction in the future.